Georgia Architectural and Historic Properties Survey of Dixie [208] Eastern portion of Dixie, Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Dixie [208] Eastern portion of Dixie, Quitman, Ga. December 1980. Rectangular plan, hipped and gabled roof. Shed porch with square posts. Shiplap siding. Sash windows with 1/1 and 2/2 lights (some have stained glass windows). Drive through on right. Interior chimneys. House set back from road in a field with oak trees leading up to it. Good condition. Date of Construction: c. 1905. The town was originally a post office stop #17, and in February of 1879, the town was named Dixie. Not significant as part of a potential National Register historic district, Dixie does not have enough historic resources to form a district.
1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 889 KB (910,957 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Quitman (Ga.)